Pengaruh Pertumbuhan Penduduk, Ketimpangan Pendapatan, dan Pengangguran terhadap Tingkat Kemiskinan di Kalimantan Selatan - Yolanda Mahrita Sari; Chairul Sa’roni (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2020)
This Study was conducted to (1) Analyze population growth, income inequality, and unemployment simultaneously on poverty levels from 2011 till 2017. (2) Analyze the variables that are most dominantly affecting poverty levels. This research used secondary data and quantitative. In this study, data generated were sourced from the Central Statistics Agency from districts/cities in South Kalimantan in 2011-2017. Data analysis technique using data panel regression analysis with random effect models. This study's results based on panel data regression analysis showed all independent variables jointly had a significant effect on poverty levels in South Kalimantan's 13 districts/cities.